Η μακροοικονομική επίδραση από διαταραχές των τιμών του πετρελαίου σε χώρες που εισάγουν και εξάγουν πετρέλαιο - Γεωργιάδου, Αδαμαντία (Τμήμα Εμπορίου, Χρηματοοικονομικών και Ναυτιλίας, Σχολή Διοίκησης και Οικονομίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Oil price shocks can affect the entire well-being of an economy. The purpose of this study is to investigate the impact of oil price shocks on gross domestic product, commercial price index and unemployment in major oil exporting countries ( Canada, Norway, UK, Russia) and major oil importing countries (Japan, Germany, USA), unlike most existing empirical literature that focuses on the oil importing US economy. A multivariate vector autoregressive analysis is used for the period over 1997:1 -2014:4, followed by Wald Granger’s causality test, Impulse Response Function (IRF) and Variance Decomposition analysis. Empirical results show that oil prices have an immediate and significant effect on GDP in both oil exporting and oil importing countries. The Granger causality test indicates that in most cases causation runs from oil price shocks to GDP, implying that oil price volatility can explain variation in GDP. The Impulse response function and variance decomposition analysis confirm that GDP seems to be affected and explained by oil price shocks, this effect being larger in oil exporting countries. Similarly, CPI is affected more by oil prices in oil exporting countries than oil importing countries. Unemployment seems to be less affected in both cases, but it may be indirectly affected as part of the economic growth.
Keywords: Oil price shocks; Vector Auto regression (VAR); Impulse response function; Wald Granger causality test; Διαταραχές των τιμών του πετρελαίου